Single-Port Laparoscopic Surgery for Inflammatory Bowel Disease. (29th April 2012) - Rijcken, Emile; Mennigen, Rudolf; Senninger, Norbert; Bruewer, Matthias
Abstract : Background . Single Port Laparoscopic Surgery (SPLS) is being increasingly employed in colorectal surgery for benign and malignant diseases. The particular role for SPLS in inflammatory bowel disease (IBD) has not been determined yet. In this review article we summarize technical aspects and short term results of SPLS resections in patients with Crohn's disease or ulcerative colitis. Methods . A systematic review of the literature until January 2012 was performed. Publications were assessed for operative techniques, equipment, surgical results, hospital stay, and readmissions. Results . 34 articles, published between 2010 and 2012, were identified reporting on 301 patients with IBD that underwent surgical treatment in SPLS technique. Surgical procedures included ileocolic resections, sigmoid resections, colectomies with end ileostomy or ileorectal anastomosis, and restorative proctocolectomies with ileum-pouch reconstruction. There was a wide variety in the surgical technique and the employed equipment. The overall complication profile was similar to reports on standard laparoscopic surgery in IBD. Conclusions . In experienced hands, single port laparoscopic surgery appears to be feasible and safe for the surgical treatment of selected patients with IBD. However, evidence from prospective randomized trials is required in order to clarify whether there is a further benefit apart from the avoidance of additional trocar incisions.